64. Transcranial magnetic stimulation in children: Collection of normative values from the lower limbs. Issue 12 (December 2016) - Testi, F.; Bastianelli, M.; Gabbanini, S.; Ammannati, A.; Cossu, C.; Del Corso, F.; Lolli, F.; Lori, S.
Abstract : The aim of this study is to collect normative data of Transcranial-Magnetic-Stimulation (TMS) in pediatric age. 46 healthy children (2–14 years, ranges: 2–5; 5–8; 8–10; 10–12; 12–14; M:F = 25:21) were tested with TMS, with an intensity stimulation of 70–80% of resting motor threshold. All children were free of neurologic, psychiatric and serious medical illness, not taking any neuropsychiatric medications, and did not have any contraindication to TMS. A statistic analysis of results noticed a correlations between the cortico-spinal conduction and the myelination of the peripheral nervous system, related with the age and height of the child. The most affected parameters results to be the Latency of the Motor Evoked Potential (L-MEP) and the Central Motor Conduction Time (CMCT). Both parameters are stable during the childhood growing progressively with the age and height. This study demonstrated how the motor conduction is closely related to the age and height of the child and, consequently, to the degrees of maturation of the nervous fibers, and how the CMCT and L-MEP are affected by the maturation of the peripheral nerves. In addition this work also emphasizes the importance of knowing the normative data of MEP in all ranges of ages to better identify the pathological findings in child's nervous system injury.